Faktor-Faktor yang Berhubungan dengan Partisipasi Ibu Balita ke Posyandu di Jorong Tarantang - Nurdin, Nurdin; Ediana, Dina; Dwi Martya Ningsih, Nila Sari (Jurnal Endurance, 2019)
Posyandu serves to facilitate the community in knowing or checking health, especially for pregnant women and children under five. in Dharmasraya the achievement of weighing D / S on toddlers is in the 12th rank out of 19 regencies / cities in West Sumatra with an achievement of 73.5%, this figure shows lower achievement if in 2013 it was 82.9%. This study aims to determine the relationship between knowledge, work, motivation and the role of cadres with the participation of mothers of toddlers visiting posyandu. The research design was descriptive analytic withdesign cross sectional. The population of this study was 108 mothers of toddlers in Tarantang Jorong. The sampling technique is simple random sampling, the sample size is 85 respondents. Data collection techniques through observation, interviews and distribution of questionnaires to respondents. Data analysis usingtest chi square. The results showed that among 85 known samples who did not participate in Keposyandu visit 55.3% (47 respondents from the analysis there was a relationship between knowledge (Pvalue = 0.021, OR = 3.098), work (Pvalue = 0.014, OR = 3.467), motivation (Pvalue = 0.003, OR = 4.332), the role of cadres (Pvalue= 0.027, OR = 2.971) participation of mother's visit to posyandu. The conclusion of the study is that there is a relationship between knowledge, work, motivation, the role of cadres and the participation of mothers of toddlers to posyandu Motivate and invite mothers to toddlers to always go to posyandu every once a month.Posyandu  berfungsi  untuk  memudahkan  masyarakat  dalam  mengetahui atau memeriksakan kesehatan terutama untuk ibu hamil dan anak balita. di Dharmasraya pencapaian penimbangan D/S pada balita berada pada rangking ke-12 dari 19 Kabupaten/Kota di Sumatera Barat dengan pencapaian 73,5%, angka ini menunjukan pencapaian lebih rendah jika dari pada tahun 2013 yaitu 82,9%. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan, pekerjaan, motivasi dan peran kader dengan partisipasi kunjungan ibu balita ke posyandu. Desain penelitian adalah deskriptif analitik dengan desain cross sectional. Populasi penelitian ini adalah 108 ibu balita di jorong tarantang. Teknik Pengambilan  sampel secara simple  random  sampling, besar sampel 85 responden. Teknik pengumpulan data melalui observasi, wawancara dan pembagian kuesioner kepada responden. Analisis data dengan menggunakan uji chi square. Hasil penelitian menunjukkan bahwa diantara 85 sampel diketahui yang tidak partisipasi dalam kunjungan  keposyandu  55,3%  (47 responden dari hasil analisis terdapat hubungan antara pengetahuan  (Pvalue= 0,021, OR =3,098), pekerjaan (Pvalue=0,014, OR=3,467), motivasi (Pvalue=0,003,OR=4,332), peran kader (Pvalue=0,027,OR=2,971) partisipasi kunjungan ibu balita ke posyandu.Kesimpulan penelitian diketahui ada hubungan antara pengetahuan, pekerjaan, motivasi, peran kader dengan partisipasi kunjungan ibu balita ke posyandu. Memberikan motivasi serta mengajak ibu balita untuk selalu ke posyandu setiap satu bulan sekali.